REFLECTION OF PROBLEM-SOLVING BY FOURTH-GRADERS IN WRITTEN AND SPOKEN SELF-ASSESSMENT SITUATIONS - Toikka, Susanna; Eronen, Lasse; Korpela, Aleksi (FMSERA Journal, 2022)
Self-assessment has significant implications for learning progress. Although speech creates a natural environment for reflection, reflection-based self-assessment is often produced by writing. Yet, support for reflection is often lacking in written self-assessment. We look at the experiences of fourth-graders (N = 22) with both spoken reflection-supported self-assessment and written reflection-unsupported self-assessment, and compare the reflections produced by different self-assessment methods. The interview study shows that reflection can be considered from the perspective of its accuracy. In turn, students compared the meaningfulness of self-assessment in terms of usability and facilitation ability of the self-assessment method. The study confirms that the success of reflection is endorsed by spoken and supported implementation of self-assessment.